Capsule Endoscopy in the Small Bowel Crohn’s Disease - Federico Argüelles-Arias; Juan Rodríguez-Oballe; Calixto Duarte-Chang; Luisa Castro-Laria; Josefa María García-Montes; Ángel Caunedo-Álvarez; Juan Manuel Herrerías-Gutiérrez (Gastroenterology Research and Practice)
CD is a chronic inflammatory disorder associated to mucosal and transmural inflammation of the bowel wall. It is well known that CD can affect the entire gastrointestinal. Therefore, ileocolonoscopy and biopsies of the terminal ileum as well as of each colonic segment to look for microscopic evidence of CD are the first-line procedures to establish the diagnosis. However, it has been observed that up to 30% of the patients have only small bowel involvement. Evaluation of the small bowel has been made with radiological procedures, barium radiography, and abdominal computed tomography or by ileocolonoscopy or enteroscopy, but they have many recognized limitations. CE is undoubtedly a very useful diagnostic tool proposed to observe small-bowel lesions undetectable by conventional endoscopy or radiologic studies. We review different studies that have been published reporting the use of CE in suspected and evaluation of the extension or the recurrence in CD and also its use in pediatric population and its complications.